2015
DOI: 10.1002/2015gl064795
|View full text |Cite
|
Sign up to set email alerts
|

Zeta potential in intact natural sandstones at elevated temperatures

Abstract: We report measurements of the zeta potential of natural sandstones saturated with NaCl electrolytes of varying ionic strengths at temperatures up to 150°C. The zeta potential is always negative but decreases in magnitude with increasing temperature at low ionic strength (0.01 M) and is independent of temperature at high ionic strength (0.5 M). The pH also decreases with increasing temperature at low ionic strength but remains constant at high ionic strength. The temperature dependence of the zeta potential can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
38
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 56 publications
(46 citation statements)
references
References 33 publications
4
38
0
Order By: Relevance
“…5. These data show that the electrical conductivity of the saturated sample increases with increasing temperature and that is consistent with that obtained in [12] To take into account the variation of the relative electric permittivity with temperature, the empirical equation mentioned in [15] is used…”
Section: Resultssupporting
confidence: 63%
See 1 more Smart Citation
“…5. These data show that the electrical conductivity of the saturated sample increases with increasing temperature and that is consistent with that obtained in [12] To take into account the variation of the relative electric permittivity with temperature, the empirical equation mentioned in [15] is used…”
Section: Resultssupporting
confidence: 63%
“…However, the results are inconsistent and contradictory. For example, some studies have found that the zeta potential increases in magnitude with increasing temperature [e.g., [7][8][9][10], while others have found that it decreases in magnitude [e.g., [11][12]. The reason for the inconsistency may be the wide range of materials and electrolyte composition used for zeta potential measurements.…”
mentioning
confidence: 97%
“…At the lower ionic strength tested (0.01 M NaCl), the zeta potential decreases in magnitude with increasing temperature, while at the higher ionic strength tested (0.5 M NaCl), the zeta potential remains constant within experimental error. This behavior is similar to that observed in natural sandstones by Vinogradov and Jackson []; they also found that the zeta potential decreased in magnitude with increasing temperature at lower ionic strength (0.01 M NaCl, consistent with that investigated here) but remained constant at higher ionic strength (0.5 M NaCl, as in this study). However, they found that the zeta potential at a given temperature was the same within experimental error across the three sandstone samples investigated.…”
Section: Discussionmentioning
confidence: 99%
“…Here μ w is the dynamic viscosity of the electrolyte, ε is the permittivity of the electrolyte, σ r is the conductivity of the sample saturated with the electrolyte at experimental conditions, and F is the intrinsic formation factor of the sample. Similar to Vinogradov and Jackson [], we obtained μ and ε as a function of temperature and ionic strength using the approach of Saunders et al [, Appendix A], and the electrical conductivity of the saturated sample σ r was measured before and after each streaming potential measurement using the approach reported in Vinogradov et al [] (Figure c). The intrinsic formation factor F at 22°C along with other key data for the Portland, Estaillades, and Ketton samples investigated was available from previous studies [ Alroudhan et al , ] (see Table S1 in the supporting information).…”
Section: Methodsmentioning
confidence: 99%
“…It is known that the mobility of particles is affected by four main mechanisms; (i) blockage, (ii) adsorption, (iii) straining, and (iv) gravity sedimentation. The adsorption effect would be small in this study because our nanoparticles are negatively charged, and the zeta potential of Berea sandstone is negative at high ionic strength 57 and in the range of pHs encountered in these experiments and in hydrocarbon reservoirs 28,58,59 . The gravity sedimentation effect is also expected to be small due to short residence time of particles in the core and the effect of Brownian motion.…”
Section: Nanoparticle Breakthrough Behaviourmentioning
confidence: 99%